2007
DOI: 10.1007/978-3-540-72200-7_5
|View full text |Cite
|
Sign up to set email alerts
|

Debugging ASP Programs by Means of ASP

Abstract: Abstract. Answer-set programming (ASP) has become an important paradigm for declarative problem solving in recent years. However, to further improve the usability of answer-set programs, the development of software-engineering tools is vital. In particular, the area of debugging provides a challenge in both theoretical and practical terms. This is due to the purely declarative nature of ASP that, on the one hand, calls for solver-independent methodologies and, on the other hand, does not directly apply to trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
72
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(72 citation statements)
references
References 12 publications
0
72
0
Order By: Relevance
“…Then, the user assigns constants to the variables occurring in r. Both steps can be assisted by filtering techniques. A stepping system can provide the user with information which non-ground rules in Π have instances that are active under Int[S] but not contained in S. This can be done using ASP itself using meta-programming and tagging transformations [5,2].…”
Section: Steppingmentioning
confidence: 99%
See 3 more Smart Citations
“…Then, the user assigns constants to the variables occurring in r. Both steps can be assisted by filtering techniques. A stepping system can provide the user with information which non-ground rules in Π have instances that are active under Int[S] but not contained in S. This can be done using ASP itself using meta-programming and tagging transformations [5,2].…”
Section: Steppingmentioning
confidence: 99%
“…Using the filtering techniques for variable substitutions, the user can be guided to a concrete active instance of c 2 , viz. to c 2 = ← empty(1, 2), empty(2, 2), empty(1, 2), empty (2,3). It is obvious that the cells (1, 2),(2, 2), (1,2), and (2, 3) do not form a valid 2 × 2 block and hence the wrong term in c 2 can be easily detected.…”
Section: Application Scenariosmentioning
confidence: 99%
See 2 more Smart Citations
“…However, practice has shown that the development of answer-set programs is not always straightforward and that programs are, as all human-made artifacts, prone to errors. In fact, debugging in ASP is currently a quite active research field [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%